Analisis Program Kampus Berdampak Terhadap Pemberdayaan Masyarakat Melalui Simase di Desa Silau Malaha - Suny Sabila; Nilam Cahya Khairani; Ariani Sahputri; Yusmalinda Yusmalinda (CV. Rumoh Aceh Publishing, 2026)
This study aims to analyze the impact of the Kampus Berdampak program on community empowerment through the development of the Simase product in Silau Malaha Village. The research focuses on five main aspects: community participation, capacity and skill enhancement, economic independence, the role of students as agents of empowerment, and sustainability strategies along with the challenges encountered. The study employs a qualitative approach, with data collected through in-depth interviews involving six informants, consisting of three villagers, two village officials (the village head and agricultural extension officer), and one community leader.The findings reveal that the community was actively involved in all stages of the program, from planning to implementation. The program successfully enhanced technical skills, digital literacy, and awareness of local potential. Independent initiatives to produce Simase have begun to emerge, although challenges remain in terms of production tools and market access. Students played a crucial role as facilitators, educators, and collaborative partners in the empowerment process. Sustainability strategies have been initiated through the establishment of community business groups and follow-up training, yet long-term success requires institutional support and cross-sector collaboration.In conclusion, the Kampus Berdampak program has proven to make a positive contribution to community empowerment based on local potential, and serves as a collaborative model between universities, communities, and village governments in promoting sustainable rural development.